THE EFFECT OF READING SHORT STORIES TO IMPROVE STUDENTS’ VOCABULARY MASTERY FOR GRADE VIII AT SMP - Anavira, Nela; Tuminah, Tuminah (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
ABSTRACT The purpose of this research was to examine how reading short stories can help eighth-grade students at Private Junior High in Sidas improve their vocabulary mastery. The context of the problem shows that students have difficulty mastering English because of conventional teaching methods. This research employed a quantitative method with an experimental design involving 34 eighth-grade students selected through cluster random sampling. The research instrument consisted of a vocabulary mastery test comprising 20 multiple-choice items covering six aspects: word definitions, synonyms, fill-in-the-blanks, antonyms, translations, and spelling. Data were analyzed using SPSS version 25 through a t-test and Cohen's d effect size. The results showed that the experimental group’s mean score increased from 42.35 in the pre-test to 67.05 in the post-test, while the control group’s score increased slightly from 46.09 to 53.44. A significant difference was found using the independent t-test (t = -3.712, p = 0.000) with an effect size of 0.92, indicating a strong practical impact. These findings confirm that the short story reading method is effective in improving students’ vocabulary mastery compared to traditional methods. The success of this method lies in its contextual learning approach and the use of explicit vocabulary teaching techniques, which make the learning process more engaging. ABSTRAK Tujuan penelitian ini adalah untuk mengkaji bagaimana membaca cerita pendek dapat membantu siswa kelas VIII di SMP Swasta di Sidas meningkatkan penguasaan kosakata. Konteks masalah menunjukkan bahwa siswa kesulitan dalam menguasai bahasa inggris karena metode pengajaran yang masih konvensional. Penelitian ini menggunakan metode kuantitatif dengan desain eksperimen, dengan 34 siswa kelas VIII sebagai sampel yang dipilih melalui teknik cluster random sampling. Instrumen penelitian berupa tes pilihan ganda sebanyak 20 soal yang mencakup enam aspek: definisi kata, sinonim, isian kosong, antonim, terjemahan, dan ejaan. Data dianalisis menggunakan SPSS versi 25 dengan uji t dan ukuran efek Cohen's d. Hasil penelitian menunjukkan bahwa skor rata-rata kelompok eksperimen meningkat dari 42.35 pada pre-test menjadi 67.05 pada post-test, sementara kelompok kontrol hanya meningkat dari 46.09 menjadi 53.44. Perbedaan signifikan ditemukan melalui uji t independen (t = -3.712, p = 0.000) dengan ukuran efek sebesar 0.92, yang menunjukkan pengaruh praktis yang besar. Hasil ini membuktikan bahwa metode membaca cerita pendek efektif dalam meningkatkan penguasaan kosakata siswa dibandingkan dengan metode tradisional. Keberhasilan metode ini terletak pada pendekatan pembelajaran yang kontekstual dan penggunaan teknik pengajaran kosakata secara eksplisit, yang membuat proses belajar menjadi lebih menarik.